Maturogenesis. Part 3. Clinical Protocol - R. Žižka; J. Šedý; J. Škrdlant; N. Němcová; T. Buchta (Czech Dental Chamber, 2016)
In the third article, the indications of revascularization treatment and possible alternative treatment options are considered. Furthermore, step-by-step clinical protocol in detail is described, with emphasis on clinical execution in every-day office of general practicioners. Irrigation protocol and intracanal medication is adjusted to obtain adequate disinfection of root canal system and at the same time the damage to dentin and stem cells is decresed. The materials which are suitable for revascularization treatment including their pros and cons are mentioned. Finally, the assesment of therapy outcomes and characterization of newly formed tissue are described.